Case report: Long-term survival in puppies assessed with echocardiography, electrocardiography and cardiac troponin I after acute death in littermates due to parvoviral myocarditis - Dines, Brenda; Kellihan, Heidi; Allen, Carolyn; Loynachan, Alan; Bochsler, Philip; Newbury, Sandra (Frontiers in Veterinary Science, 2023)
Positive clinical outcomes of a group of surviving puppies from a litter affected by parvoviral myocarditis are detailed in this case report. Past reports focus on the negative outcomes of littermates of puppies who have died of parvoviral myocarditis. In this case, two puppies in a shelter setting, from a litter exposed to parvovirus, died suddenly with parvoviral myocarditis diagnosed at necropsy. The other seven puppies were screened for cardiac health with echocardiogram, electrocardiogram, and cardiac troponin I prior to adoption. All seven puppies had normal echocardiograms, electrocardiograms, and normal initial and recheck cardiac troponin I results. At recheck two years after the initial round of testing, two of the puppies were screened and continue to have normal cardiac diagnostics. All seven dogs are alive and thriving at five years old in homes with adopters who were given a complete medical history on the dogs prior to adoption. In summary, the outcomes for puppies in litters affected by parvoviral myocarditis are variable but they do not have to be grave. The use of cardiac diagnostics including echocardiogram, electrocardiogram and cardiac troponin I may serve as a prognostic basis for assessing the potential outcomes for the surviving puppies in affected litters.